Medical students’ attitudes towards increasing early clinical exposure to primary care - van Oppen, James; Camm, Charlotte; Sahota, Gurvinda; Taggar, Jaspal; Knox, Richard (Taylor & Francis, 2018)
Context: The sustainability of the future UK General Practice (GP) workforce is reliant on half of medical graduates choosing a career in primary care (1), but while good quality undergraduate GP placements (particularly those which are early in the curriculum and integrated into ongoing learning) have been linked to subsequent GP career choices (2), exposure has plateaued at 13% of UK undergraduate teaching time(3).Of students in UK medical schools, undergraduates at the University of Nottingham(UON) spend towards the least amount of time in primary care. Research questions: We set out to investigate Nottingham medical students’ attitudes towards a proposed increase in the primary care component of their “early clinical exposure” module from ten half days to fourteen full days during the first two years of the undergraduate course. We sought to assess the potential impact on perceived student learning and experience. Description: We recruited nine students from across the five undergraduate year groups to take part in audio-recorded semi-structured interviews which lasted 30-60 minutes. All participants provided informed consent. Having set out to include 20-30 participants in our sample, recruitment was impaired by students’ busy teaching schedules and overlapping exam seasons within the University. Interviews followed a theme guide and explored topics of exposure time, learning opportunities, and career intentions. We analysed verbatim transcripts using a constant comparative approach, assigning and grouping codes, and merging and revising categories until new data did not alter the resultant themes. We considered data to be saturated once ideas were repetitively expressed and did not prompt revision of themes. A larger sample would have strengthened confidence in our theoretical integrity. Outcomes: Students reported that opportunities encountered in primary care settings allowed them to contextualise their scientific learning and develop core practical and communication skills (Table 1). Their GP placements were multi-disciplinary and holistic, enabling them to build professional relationships with mentors and ultimately feel better-prepared for both their undergraduate clinical phase and future careers. Immersing students into the clinical environment at this early stage of their training provided drive and focus for their academic studies, but some students shared their awareness of a stressful GP workplace with time and administrative pressures, reflecting how this experience discouraged them from choosing GP careers. Participants unanimously supported an expansion to the timetabled early primary care clinical exposure.